The Role of CEO Power and Foreign Ownership in the Selection of Public Accounting Firms and the Effectiveness of the Audit Committee as Moderators - Dede Nursaman; Harnovinsah; Nurmala Ahmar (LPPM Universitas Terbuka, 2023)
The purpose of this study is to analyze the role of CEO power and foreign ownership of the election a Public Accounting Firm (KAP) and the effectiveness of the Audit Committee as a moderator. The research objects used are companies that are included in the IDX80 index on the Indonesian Stock Exchange 2017-2021. Based on the purposive sampling technique, sample of 42 companies was obtained which were considered to meet the criteria as research objects. The analytical method used in this study is Structural Equation Modeling (SEM) with SmartPLS 3 software. The results show partially that the higher the CEO power, foreign ownership and foreign ownership moderated by the effectiveness of the Audit Committee, the company more likely choose Big 4 KAP as external auditors. Meanwhile, the higher the CEO power, which is moderated by the effectiveness of of the Audit Committee, more likely choose non-Big 4 KAP.